Experimental research of efficiency increasing method for qutrits quantum cryptography protocols - Гнатюк, Сергій Олександрович; Жмурко, Тетяна Олександрівна; Кінзерявий, Василь Миколайович; Юбузова, Халіча Ібрагімівна (Ukrainian Information Security Research Journal, 2016)
Today acutely raises the issue of providing information confidentiality in conditions of growth quantity and quality of violations in cyberspace that are constantly improving and developing. Reliability of traditional methods for ensuring confidentiality is questionable taking into account contemporary threats. So look for alternative methods and means of security is urgent issue. Significant interest causes quantum cryptography, which do not depend on computing or other capabilities of offender, uses specific unique properties of quantum particles, and based on the inviolability of the laws of quantum physics. One of the most advanced technology of quantum cryptog-raphy is quantum secure direct communication, which can transmit information directly by open channel (without encryption – in this case there is no key distribution problem), but they have only asymptotic resistance to noncoherent attacks and, certainly requires some methods for amplification security. In this regard, developed a method of ensuring the stability of quantum cryptography protocols. To evaluate the effectiveness of this method was developed a methodology for conducting experimental research, according to which it is made comparing of its performance with known method. According to the obtained results, the proposed method has a speed in 1.52 times faster against analogs at the same level of resistance to noncoherent attacks.